2010
DOI: 10.1111/j.1600-0528.2009.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting tooth loss for older adults with special needs

Abstract: An evidence-based model with eight predictors was developed to quantitatively predict risk of tooth loss for OASN at the individual level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…A detailed description regarding study subjects, sample selection and data collection has been reported previously [18]. To facilitate discussion, the materials and methods are briefly described below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description regarding study subjects, sample selection and data collection has been reported previously [18]. To facilitate discussion, the materials and methods are briefly described below.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the detailed tooth loss pattern in older adults with special needs remains unclear. Although multiple factors, such as old age [13-14, 16, 18], sociodemographic characteristics [18], poor oral health condition [13,18], cognitive impairment [17], physical disability [14,[18][19], systemic health and so on [13,17], are considered to be associated with tooth loss in special-needs individuals, how these risk factors interactively and synergistically affect tooth loss in these individuals remains unknown. The lack of understanding on these issues not only increases difficulty for dental professionals in managing tooth loss and associated oral dysfunction for older adults with special needs, but also affects quality of care for these vulnerable individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed characteristics of the study participants have been reported previously 20 . To facilitate the discussion, participant characteristics are briefly described here.…”
Section: Resultsmentioning
confidence: 99%
“…The institutional review board of the University of North Carolina approved the study protocol. The detailed materials and methods of this study have been reported previously 20 …”
Section: Methodsmentioning
confidence: 99%
“…30,31 Tooth loss is the result of a number of factors, including the cumulative effects of dental disease, reduced salivary flow, 32 provider treatment preferences, and patient factors, including health literacy and financial concerns. The increased prevalence of chronic conditions among older as compared with younger adults 33 may also contribute to the decision to retain or extract teeth.…”
Section: Discussionmentioning
confidence: 99%